Pengaruh Coating Telur Asin Terhadap Umur Simpan - Mulyati, Sri; Tamrin, Tamrin; Asmara, Sandi; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2026)
Eggs are one of the most preferred sources of protein by people in Indonesia because of their high nutritional content and affordable prices. Purebred chicken eggs are easy to find in various places such as stalls, traditional markets, to supermarkets. Even though there is a lot of demand, purebred chicken eggs have a shelf life that doesn't last long and is easily damaged. The duration of egg storage will result in decreased egg quality so it is necessary to have a process that can extend the shelf life of the eggs, one of which is by salting the eggs. Marinated chicken eggs are made by soaking in a salt solution. However, the shelf life of the salted eggs can only last for about 3 weeks. This study aims to study the effect of coating on salted chicken eggs on shelf life, changes in weight, aroma, color, taste, and texture of salted chicken eggs. This study used a randomized block design (RBD) with 3 coating treatments and 3 coating concentration treatments, repeated 3 times. Salted eggs with tapioca flour coating treatment with concentrations of 2%, 4%, 6% can last for 13 days, 34 days, and 23 days. Then the beeswax coating treatment with a concentration of 2%, 4%, 6% can last for 20 days, 22 days, and 18 days. Then the chitosan coating treatment with a concentration of 2%, 4%, 6% can last for 20 days, 22 days and 21 days. Based on this study, it can be concluded that tapioca flour coating with a concentration of 4% had an effect on shelf life, aroma, color, taste and texture of salted chicken egg but had no effect on changes in weight.